Risks to global water resources from geoengineering the climate with solar radiation management - Burnell, Lorna (2021)
Climate change, including global temperature rise, is one of the greatest threats facing humanity and the planet. The response of the collective human population to reduce greenhouse gas emissions, the driver of this change, has been far from adequate. To this end, methods of geoengineering the climate have been proposed, ranging from removal of carbon dioxide presently in the atmosphere (including Carbon Capture and Storage and Direct Air Capture) to methods of adjusting the amount of incoming solar radiation reaching the troposphere. Solar geoengineering (SG), also known as solar radiation management (SRM), is a proposed method of geoengineering which reflects a portion of incoming solar radiation back into space to slow or reverse global temperature rise. However, whilst simulations suggest that SG may be able to halt global mean temperature changes, it will not be able to counteract all aspects of climate change which threaten both society and ecosystems. One particularly well-known effect of current SG modelling experiments is that, when designed to offset a specific temperature rise under greenhouse gas forcing, precipitation values would be excessively offset and decrease below the baseline, reducing the overall intensity of the global hydrological cycle. A global-scale assessment is urgently needed to quantify the risks and opportunities SG poses to global water resources.